Childhood and power. Michel Foucault’s contributions to an Anthropology of infancy from a Biopolitical approach - Ramos Gómez, Felipe Manuel (2025)
A long tradition of research in Pediatrics, Psychology, Pedagogy, Anthropology, and the broader biomedical field has focused on childcare. Yet, the experiences, subjectivity, and agency of childhoods have been subordinated to regulatory norms and statistical measures, objectified for a stereotypical view emphasizing docility and utility. This study positions Biopower and Biopolitics, central concepts in Foucault’s Works, as technologies that have solidified this image. It underscores the ongoing need for a critical genealogy of research on diverse childhoods to challenge these dominant narratives.